Aspectos culturais e interculturais nos livros didáticos de língua estrangeira: italiano e inglês em confronto - Adriana Mendes Porcellato (2013)
The relation between language and culture surfaces in the foreign language classroom, where not only the language but also the cultural aspects related to it are taught and learned. This work shows how the cultural and intercultural components are presented in the Italian and English language coursebooks. The three best-selling Italian and English textbooks in Brazil were chosen as the corpus for the study, which contemplated a total of six textbooks. Based on these books, qualitative and quantitative analyses were carried out with the intention of clarifying the main differences in the target culture representation in the coursebooks of the two languages as well as of understanding whether the authors include activities that promote the intercultural approach in their textbooks. The analyses were carried out with checklists which were developed in similar studies and were underpinned by a conception of culture as a way of living, considering Morans (2001) definition, and by concepts such as Hymes (1969) Communicative Competence and Byrams (1997) Intercultural Communicative Competence. The results have shown that there are indeed differences in the way the coursebooks of the two languages treat the cultural component: the Italian books focus on the culture related to Italy, as if this country were a commodity, while the English books consider the language as a lingua franca and, by representing different English-speaking and non English-speaking countries, end up conveying a superficial and fragmented idea of culture. Based on the collected data, we observed that there are also similarities among the textbooks, especially as they all integrate the linguistic and cultural aspects. Finally, in our corpus we noticed that there is hardly any interest in promoting intercultural competence in the students.